Conditional Sponsorship Agreement between Demos Cafe and Student Activities on Sharia Economic Law Perspectives - Putri Tasela Ayu; Nasrudin; Dian Herdiana (STAI Al-Mas'udiyah, 2026)
This study aims to analyse conditional sponsorship practices in the Muamalah Fair 2025 student activities and examine their compliance with the principles of Islamic economic law. This study employs an empirical juridical approach and a descriptive-analytical research method, collecting data through literature and field research, including interviews with the committee, observations of the implementation of sponsor cooperation, and analyses of documents such as MoUs. The results show that sponsorship for the Muamalah Fair 2025 is formally structured as conditional grants. However, several conditions set by the sponsor, which require the recipient to provide positive ratings and reviews on the sponsor's Google page, indicate a substantive exchange of benefits. This condition raises ethical issues in muamalah because it has the potential to contain elements of tadlis or dishonesty, shifting the character of the contract from what was originally tabarru’ (a contract of charity that does not aim to obtain rewards) to mu’awadhah (a contract of exchange that contains reciprocal benefits) that is veiled. The novelty of this research lies in its specific analysis of conditional sponsorship practices in student activities, linking empirical field findings with the construction of conditional grant theory in Islamic economic law. The contribution of this research is expected to serve as a reference for future research with similar correlations.